Gay voices without intersectionality is White supremacy: narratives of gay and lesbian teachers of color on teaching and learning. Issue 6 (2nd July 2020) - Bracho, Christian A.; Hayes, Cleveland
Abstract: The primary objective of this collection is to document the lived experiences of queer teachers of color who work in P-20 education, as a means of identifying and analyzing how the intersections of race, gender, and sexuality impact teaching dispositions and lived struggles. Similar to Anzaldua, Tate, and Valadez and Elsbree call for 'queer border crossings', working across epistemological boundaries and frameworks; the articles presented here cross many disciplinary borders by connecting with individuals across different cultural contexts, in effect breaking pervasive silences of LGB people of color in educational research.